2018
DOI: 10.1016/j.jrras.2017.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of radioactivity concentration in soil samples around phosphate rock storage facility in Richards Bay, South Africa

Abstract: Mining, mineral processing and industrial activities have long been linked to increased levels of radioanuclides in soil in their vicinity. In this work, concentrations of naturally occurring radionuclides in soil samples collected around a rock phosphate storage facility in Richards Bay in South Africa were determined. A total of 90 soil samples were collected and analyzed for 238 U and 232 Th using neutron activation analysis and 226 Ra and 4 K using a HPGe detector. The results revealed the average radioact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 9 publications
(14 reference statements)
0
18
0
Order By: Relevance
“…These usually lead to the spread of NORMs contaminating the environment and subsequently results in potential radiation exposure of workers and member of the general public. Although research has reported the radionuclide content of the rock phosphate stored in this study area (Masok et al, 2016a) and the quality of water within Richards Bay (Lin, Biyela, Puckree, & Bezuidenhout, 2004;Masok, Masiteng, Mavunda, Maleka, 2017a;Masok, Masiteng, Mavunda, Maleka, Winkler, 2017b;Vetrimurugan, Brindha, & Elango, 2017), no available literature is published about the concentration of radionuclides in soil within the precinct of this rock phosphate storage facility. This study is intended at bringing to light the concentration of parent radionuclides in soil around the rock phosphates storage facility at Richards Bay with an aim to map out hot spots in term of radioactivity concentration level.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…These usually lead to the spread of NORMs contaminating the environment and subsequently results in potential radiation exposure of workers and member of the general public. Although research has reported the radionuclide content of the rock phosphate stored in this study area (Masok et al, 2016a) and the quality of water within Richards Bay (Lin, Biyela, Puckree, & Bezuidenhout, 2004;Masok, Masiteng, Mavunda, Maleka, 2017a;Masok, Masiteng, Mavunda, Maleka, Winkler, 2017b;Vetrimurugan, Brindha, & Elango, 2017), no available literature is published about the concentration of radionuclides in soil within the precinct of this rock phosphate storage facility. This study is intended at bringing to light the concentration of parent radionuclides in soil around the rock phosphates storage facility at Richards Bay with an aim to map out hot spots in term of radioactivity concentration level.…”
Section: Introductionmentioning
confidence: 92%
“…A total of ninety soil samples were collected from 30 sampling positions spread across the coal area (Area 1), the rock phosphate storage area (Area 2) and undisturbed area called the control area (Area 3). The location of all sampling positions are fully shown on the map of the study area in our previous publication (Masok et al, 2017b).…”
Section: Sampling Techniques and Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been made in many countries to determine the concentration of the natural radionuclides in rock samples, e.g. Masok, Masiteng, Mavunda, Maleka, and Winkler (2018), Prakash, Kaliprasad, and Narayana (2017), and Uosif, Hashim, Issa, Tamam, and Zakaly (2016). The objectives of the present study were to determine metal composition and measure the natural radioactivity levels of 226 Ra, 232 Th, and 40 K in rock samples collected from an important site in Saudi Arabia (Haradh region) also to assess the radiological hazard indices in the air and to compare the results with international levels.…”
Section: Introductionmentioning
confidence: 99%